Upaya Bendahara Lembaga Pemasyarakatan dalam Menyikapi Budaya Korupsi di Masyarakat - Ghofar Syafri Hudzaifi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The culture of corruption that is pervasive in Indonesian society presents major challenges for Correctional Institutions, especially in maintaining financial integrity. The prison treasurer has a strategic role in responding to this phenomenon through a series of steps such as implementing a transparent financial management system, increasing strict internal supervision, and regular training for employees regarding ethics and integrity. Apart from that, community involvement and collaboration with external institutions are also needed to strengthen accountability and ensure that efforts to eradicate corruption are effective. Through a comprehensive and collaborative approach, prisons strive to create an environment that is clean and free from corruption. These efforts are not only focused on internal reform, but also on strengthening relations between government institutions, civil society and the private sector, in order to build a system that is more accountable and has high integrity. In the midst of existing progress, significant challenges still hinder this effort, but multidimensional efforts are expected to provide long-term positive impacts.